PERAN KELOMPOK TANI TERHADAP PENDAPATAN PETANI PADI SAWAH DI DAERAH IRIGASI TEKNIS KECAMATAN KAMBERA KABUPATEN SUMBA TIMUR - Ferdinand Mangutu Kiki; Elfis Umbu katongu Retang; Junaedin Wadu (Universitas Galuh, 2022)
This studi aims to determine the role of farmer groups on the income of rice farmers in the technical irigation area Kambera District East Sumba Regency. This research was conducted for 2 months from may to july 2021. The data used in this study are primary data and secondari data. The result of this study indicate the role of farmer groups as a learning class to get a score of 312 with a role category. The role of farmer groups as a forum for cooperation received a score of 286 in the category of quite role and the role of farmer groups as a production unit scored 257 in the category of playing a sufficient role.based on the results of the recapitulation of the role of farmer groups, it obtained a score of 287 which indicates that the farmer groups have quite a role as a learning class, a forum for cooperation and production unit. While the incomes of rice farmers can be seen by using income analysis. The resultsof this study indicate that the average cost incurred by farmers is Rp.10.256.325,00/ Ha and ravenue of Rp.20185.818,00/ Ha so that the income of rice farmers in the technical irrigation area of the Kambera sub-district is Rp.10.525.493,00/Ha. To determinate the role of farmer groups on income, the spearman rank correlation test was used using SPSS.16 which showed that the role of farmer groups had a significant effect on the income of lowland rice farmers. The more the role of farmer groups is increased, it will increased the income of rice farmers in the technical irrigation area of the Kambera Sub-district.